Factors affecting the purchasing intention on all-you-can-eat restaurants in Iloilo City - Ignacio, Michael D.; Legaste, Queenie Hope S.; Parungao, Micah Jean L.; Peniano, Ma. Ceniella G.; Perbillo, Maye Therese L.; Sermona, Mavy Lou S. (2019)
Food away from home consumption has been a trend especially in metropolitan urban cities due to time constraint. Along with this trend, is the rising of the buffet services in the country and specifically in Iloilo City. The food industry continues to flourish in the city and food establishments having a rather rigid competition. However, studies regarding all-you-can-eat buffets in Iloilo City are just few. So as to bridge the gap, the researchers would want to assess why patrons staying in Iloilo City would want to avail to the services of all-you-can-eat restaurants. With this study, the researchers may be able to recommend the necessary and the all-you-can-eat buffet restaurant needs. The nature of the study is a mixture of both quantitative and qualitative. The conceptual framework used in the study was anchored with the model of Theory of Planned Behavior of Ajzen (11985) as well as his works with Fishbein (1980). For the quantitative part, a survey was done to 100 convenient sampling respondents in order to assess whether their attitude, the subjective norms, and the perceived behavioral controls towards buffet services affect their purchase intention. Moreover, survey questions regarding consumer response towards the marketing strategies of these buffets were asked in order to know whether these strategies affect their intention to purchase. For the qualitative part, Key Informant Interviews (Kils) were conducted for the establishments management to assess the different marketing strategies the establishments employs particularly their promotions. After conducting the study, the result showed that customers' age has a significant effect on their perceived behavioral control over all-you-can-eat buffet. Most of the respondents are millenials and they are mostly students and young professionals who are conscious with their budget and are not financially stable for now. Also, customers' sex have shown a significant effect on the perception towards the marketing strategies of the companies. Men and women want different things out of a buying decision. Customarily the obtaining choice is to move from client attention to enthusiasm for acquiring lastly narrowing of alternatives (Kraft, 2012). The two key informant, believe that ambience is the factor that mostly influences the Customer's intention to purchase in all-you-can-eat buffet serviced. According to them most of their customers go with their friends or with their family. The marketing strategies that they implement depends on their target market. One of them gives great importance in radio advertisements since they are targeting the older generations. They both consider social media as an important platform to promote their restaurant. The researchers strongly recommend that if the establishments target customers are millenials or families, they should intensify their marketing strategies in social media and further enhance and update their websites. Moreover, they should incorporate group discount packages in their promotional strategy. Thus, these type of companies must continue to capture the attention of women and should adjust their marketingplans so that it will capture men's attention as well. Also, buffet companies do not have to invest in celebrity endorsements since these will not really affect the decisson of their target market to purchase again.
Research Paper (BS Maanagement). -- [Iloilo City] : UPV-CM, June 2019.